Synthesis of Hierarchically Porous Metal Oxide Monoliths via Sol–Gel Process Accompanied by Phase Separation From Divalent Metal Salts: A Short Review - Lu, Xuanming; Nakanishi, Kazuki (Frontiers in Chemical Engineering, 2021)
The sol–gel process accompanied by phase separation is one of the methods to prepare hierarchically porous monoliths, HPM, which is applicable not only to oxides but to various materials compositions such as metal phosphates, organic-polymers/carbons, metal-organic frameworks. It is not until recently, however, that progress has been made in the preparation of low-valence metal oxide HPMs, such as those of magnesium, manganese, cobalt, nickel, etc. Due to the difficulty of divalent metal precursors to form homogeneous gels, different approaches from those established for trivalent and tetravalent counterparts have been attempted. This short review introduces the methods and trials in the preparation of metal oxide HPMs from divalent metal salts.